2019
DOI: 10.1155/2019/3105817
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Protein C Receptor Could Contribute to Experimental Malaria-Associated Acute Respiratory Distress Syndrome

Abstract: The severity of Plasmodium falciparum malaria is associated with parasite cytoadherence, but there is limited knowledge about the effect of parasite cytoadherence in malaria-associated acute respiratory distress syndrome (ARDS). Our objective was to evaluate the cytoadherence of infected red blood cells (iRBCs) in a murine model of ARDS and to appraise a potential function of endothelial protein C receptor (EPCR) in ARDS pathogenesis. DBA/2 mice infected with P. berghei ANKA were classified as ARDS- or hyperpa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 66 publications
2
14
0
Order By: Relevance
“…Authors suggested that high levels of sEPCR in these group could be secondary to TNF-alpha associated EPCR dysfunction [ 24 ]. Similar findings were reported in two different studies evaluating septic shock patients secondary to pneumococcal pneumonia and experimental malaria-associated ARDS model [ 21 , 22 ]. These findings support the view that there is an intersection between coagulation and inflammation cascade in systemic infectious diseases with severe lung involvement and that protein C system located at this junction.…”
Section: Discussionsupporting
confidence: 90%
“…Authors suggested that high levels of sEPCR in these group could be secondary to TNF-alpha associated EPCR dysfunction [ 24 ]. Similar findings were reported in two different studies evaluating septic shock patients secondary to pneumococcal pneumonia and experimental malaria-associated ARDS model [ 21 , 22 ]. These findings support the view that there is an intersection between coagulation and inflammation cascade in systemic infectious diseases with severe lung involvement and that protein C system located at this junction.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are compatible with our results since the ARDS-developing mice present an increase in vascular permeability evidenced by pleural effusion reaching 1 ml of fluid in the thoracic cavity, which would complicate compliance. Our previous results showed increased pulmonary vascular permeability in malaria infection in DBA/2 model both in vivo and in vitro [4,5,38,39]. In addition, we observed that, after 14 th dpi, an improvement in lung aeration when compared to that on the 7 th dpi.…”
Section: Plos Onesupporting
confidence: 50%
“…Mortality was monitored from the 5 th to 17 th day post infection (dpi). The experimental time course to was reduced to 17 days after infection, compared with other experiments of our model previously published [5,[37][38][39] to shorten any discomfort, pain or suffering that Plasmodium berghei infection may cause.…”
Section: Plasmodium Berghei Anka Infection Parasitemia and Euthanasiamentioning
confidence: 93%
See 1 more Smart Citation
“…Protein C has also been found to be an independent predictor of mortality for ALI/ARDS [ 130 , 208 ]. Mice with malaria-associated ARDS showed an increase in EPCR concentrations in lung homogenates [ 209 ], whereas loss of EPCR and TM was seen in lung specimens from patients who died from severe falciparum malaria with coexisting ARDS [ 210 ].…”
Section: Pulmonary Endothelial Functionsmentioning
confidence: 99%